A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.

HLA-G regulatory polymorphisms are associated with susceptibility to HCV infection. - Catamo, E; Zupin, L; Freato, N; Polesello, V; Celsi, F; Crocè, S L; Masutti, F; Pozzato, G; Segat, L; Crovella, S (HLA, 2017)
BACKGROUND: Hepatitis C virus (HCV) is able to bypass the immune system modulating innate and adaptive immune response and blocking T helper 1 (Th1) cell production. Because the human leukocyte antigen (HLA)-G molecule has immunomodulatory properties inhibiting the function and production of natural killer and cytotoxic lymphocyte T cells, as well as promoting shift from Th1 toward Th2 response, we hypothesized its involvement in susceptibility to HCV infection. MATERIALS AND METHODS: Considering that HLA-G mRNA expression has been reported to be under genetic control, an association study was conducted analyzing 800 base pairs upstream the ATG at the 5'upstream regulator region (URR) and 850 base pairs from ATG to exon 3 and the 3'untranslated region (UTR) of HLA-G gene in Italian HCV-positive patients and uninfected controls. RESULTS: Four 5'URR polymorphisms (-725C>G>T, -509C>G, -400G>A and -398G>A), 7 polymorphisms at coding region (+15G>A, +36G>A, +243G>A, insC506, 531G>C, delA615 and 685G>A), the +644G>T polymorphism, and 1 haplotype (TTGTTCCIGAC) showed different frequency distributions between HCV patients and uninfected controls. CONCLUSION: The results from our study suggest a possible involvement of HLA-G in the risk modulation toward HCV infection.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Exons; Female; Gene Expression; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Haplotypes; Hepacivirus; Hepatitis C; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk; Th1 Cells

LTF and DEFB1 polymorphisms are associated with susceptibility toward chronic periodontitis development. - Zupin, L; Robino, A; Navarra, C O; Pirastu, N; Di Lenarda, R; Gasparini, P; Crovella, S; Bevilacqua, L (Oral Dis, 2017)
OBJECTIVES: Chronic periodontitis is a common pathological condition that affects the supporting tissue of the teeth, leading to progressive alveolar bone destruction and teeth loss. The disease is caused by bacteria and derives from an altered host immune and inflammatory response, also involving different factors such as the oral hygiene, smoking, and genetic background. The innate immune response, the first line of host defense, could also play an important role in the susceptibility to chronic periodontitis. In this study, we evaluated the possible association between periodontal disease and seven genetic variations within DEFB1 and LTF genes, encoding for β-defensins 1 and lactoferrin (two members of oral innate immune system), in an Italian isolated population. SUBJECTS AND METHODS: DEFB1 5'UTR g. -52G>A (rs1799946), g. -44C>G (rs1800972), g. -20G>A (rs11362), 3'UTR c*5G>A (rs1047031), c*87A>G (rs1800971), LTF p.Ala29Thr (rs1126477), and p.Lys47Arg (rs1126478) single nucleotide polymorphisms (SNPs) were analyzed in 155 healthy individuals and 439 chronic periodontitis patients from North-East Italy. RESULTS: Significant associations were found between periodontitis and g. -20G>A (rs11362) and g. -44C>G (rs1800972) SNPs in DEFB1 gene as well as p.Ala29Thr (rs1126477) and p.Lys47Arg (rs1126478) SNPs in LTF gene. DISCUSSION: Our results suggest the involvement of DEFB1 and LTF genetic variations in the susceptibility toward development of periodontitis.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; beta-Defensins; Case-Control Studies; Chronic Periodontitis; Female; Genetic Predisposition to Disease; Humans; Lactoferrin; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Polymorphisms in key bone modulator cytokines genes influence bisphosphonates therapy in postmenopausal women. - Lima, C A D; Javorski, N R; Souza, A P O; Barbosa, A D; Valença, A P M C; Crovella, S; Souza, P R E; de Azevêdo Silva, J; Sandrin-Garcia, P (Inflammopharmacology, 2017)
Osteoporosis is a multifactorial and debilitating disease resulting from decreased bone mineral density (BMD) and loss of tissue microarchitecture. Ineffective therapies may lead to bone fractures and subsequent death. Single nucleotide polymorphisms (SNPs) in key immune regulator genes have been associated with therapeutic response to bisphosphonates, which are the first therapeutic line of choice for osteoporosis. However, cytokine pathways and their relation with therapeutic adhesion remain to be fully elucidated. Aimed at better understanding these processes, we investigated the response to bisphosphonate therapy in postmenopausal women and four SNPs in key proinflammatory cytokines genes: IL23R +2284 (C>A) (rs10889677), IL17A +672 (G>A) (rs7747909), IL12B +1188 (T>G) (rs3212227) and INF-γ -1616 (G>A) (rs2069705). A total of 69 patients treated with bisphosphonate were followed for a period of 1 up to 4 years, genotyped and compared according to their changes in bone mineral density (BMD) and level of biochemical markers during their treatment. The INF-γ -1616 G/G associated with increased BMD values in femoral neck (GG/AA, p = 0.016) and decreased BMD values in total hip (GG/GA, p = 0.019; GG/AA, p = 0.011). In relation to biochemical markers, INF-γ -1616 SNP associated with increased alkaline phosphatase (GG/AA; p < 0.0001) and parathyroid hormone levels (AA/GA; p = 0.017). Vitamin D values changes were related to IL17A +672 (GG/GA, p = 0.034) and to IL12B +1188 (TT/TG, p = 0.046) SNPs. Besides, significant differences in changes of calcium levels correlated with IL23R +2284 (CC/CA, p = 0.016) genotypes. Altogether, we suggest that these polymorphisms may play an important role for therapeutic decisions in osteoporosis treatment.
Keywords: Aged; Bone Density; Bone Remodeling; Cytokines; Diphosphonates; Female; Humans; Middle Aged; Osteoporosis, Postmenopausal; Polymorphism, Single Nucleotide; Postmenopause

Association of the HLA-G 3'UTR polymorphisms with colorectal cancer in Italy: a first insight. - Garziera, M; Catamo, E; Crovella, S; Montico, M; Cecchin, E; Lonardi, S; Mini, E; Nobili, S; Romanato, L; Toffoli, G (Int J Immunogenet, 2016)
This study aimed to explore functional and regulatory polymorphisms and haplotypes at the HLA-G 3'UTR region in colorectal cancer development. The presence of nonpolymorphic variants was also evaluated. Three-hundred and eight patients with colorectal cancer and 294 healthy controls were analysed at the germinal level. We found an association with increased risk of colorectal cancer for +2960 14-bp INDEL, +3196 C>G SNPs and UTR-2 haplotype, and a 'protective' role for +3003 T>C, +3010 C>G polymorphisms and UTR-4 haplotype. We detected in 3 distinct patients, a novel nucleotide change (+3037 C>A) and 2 already described rare variants, +3032 G/C (EUR MAF = 0.1%) and +3092 G/T (EUR MAF = 0%). This is the first study showing associations between different polymorphisms in the HLA-G 3'UTR and colorectal cancer susceptibility.

MBL2 Genetic Variants in HCV Infection Susceptibility, Spontaneous Viral Clearance and Pegylated Interferon Plus Ribavirin Treatment Response. - Zupin, L; Polesello, V; Alberi, G; Moratelli, G; Crocè, S L; Masutti, F; Pozzato, G; Crovella, S; Segat, L (Scand J Immunol, 2016)
Hepatitis C is disease that damages the liver, and it is caused by the hepatitis C virus (HCV). The pathology became chronic in about 80% of the cases due to virus persistence in the host organism. The standard of care consists of pegylated interferon plus ribavirin; however, the treatment response is very variable and different host/viral factors may concur in the disease outcome. The mannose-binding protein C (MBL) is a component of the innate immune system, able to recognize HCV and consecutively activating the immune response. MBL is encoded by MBL2 gene, and polymorphisms, two in the promoter region (H/L and X/Y) and three in exon 1 (at codon 52, 54 and 57), have been described as functionally influencing protein expression. In this work, 203 Italian HCV patients and 61 healthy controls were enrolled and genotyped for the five MBL2 polymorphisms mentioned above to investigate their role in HCV infection susceptibility, spontaneous viral clearance and treatment response. MBL2 polymorphisms were not associated with HCV infection susceptibility and with spontaneous viral clearance, while MBL2 O allele, O/O genotype, HYO haplotype and DP combined genotype (all correlated with low or deficient MBL expression) were associated with sustained virological response. Moreover, a meta-analysis to assess the role of MBL2 polymorphisms in HCV infection susceptibility was also performed: YA haplotype could be associated with protection towards HCV infection.

Role of inflammasome genetics in susceptibility to HPV infection and cervical cancer development. - Pontillo, A; Bricher, P; Leal, V N C; Lima, S; Souza, P R E; Crovella, S (J Med Virol, 2016)
PROBLEM: Only a small proportion of HPV+ women develop virus-associated lesions and cervical cancer, suggesting that other factors are involved in HPV+ keratinocyte transformation. Immune response plays an important role in clearing HPV infection, and host genetic variants resulting in defective immune response have been associated with virus persistence and/or cervical cancer. Considering that genetic variations in inflammasome genes were previously associated with viral infection and cancer development, the present study investigates selected single nucleotide polymorphisms (SNPs) in inflammasome genes as a possible risk factor for HPV infection susceptibility and/or for progression to cervical cancer. PATIENTS AND METHODS: 12 SNPs in seven inflammasome-related genes (NLRP1, NLRP3, NLRP6, CARD8, IL1B, IL18, TNFAIP3) were genotyped in a Brazilian HPV+ case/control cohort (n = 246/310). Multivariate analysis was performed in case/control as well as in HPV+ women stratified by the presence or severity of histologic lesion, HPV persistence, and type of virus. RESULTS: IL1B rs1143643 was associated with protection against HPV infection in case/control analysis. NLRP1 rs11651270 plays a protection role against HPV persistence and/or oncogenesis. NLRP3 rs10754558 and IL18 rs1834481 exert a beneficial role against HPV persistence. NLRP3 rs10754558 variant resulted significantly associated with a lower risk to be infected with a high-risk HPV. CONCLUSION: Our findings for the first time demonstrated that inflammasome genetics could affect HPV/host interaction in terms of virus susceptibility as well as of virus/persistence and cervical cancer progression. J. Med. Virol. 88:1646-1651, 2016. © 2016 Wiley Periodicals, Inc.

Comprehensive analysis of polymorphisms in the HLA-G 5' upstream regulatory and 3' untranslated regions in Brazilian patients with systemic lupus erythematosus. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Tavares Dantas, A; de Ataíde Mariz, H; Ferreira da Rocha Junior, L; Branco PintoDuarte, A L; Coelho, A V C; de Moura, R R; Polesello, V; Crovella, S; et al. (Tissue Antigens, 2015)
This study aims to comprehensively analyze human leucocyte antigen (HLA)-G polymorphisms association with susceptibility to systemic lupus erythematosus (SLE) development and clinical manifestations. The HLA-G 5' upstream regulatory region (URR), 3' untranslated region (UTR) and a cytosine deletion at exon 3 (ΔC, HLA-G*0105N allele) were analyzed in 114 SLE patients and 128 healthy controls from North East Brazil. The +3003T>C (rs1707) C allele and the HG010101c extended HLA-G allele were significantly more frequent in SLE patients than healthy controls (+3003C allele frequency: 12% in SLE patients vs 6% in controls; odds ratio (OR), 2.10, 95% confidence interval (CI), 1.06-4.28, P = 0.026; HG010101c frequency: 11.8% in SLE patients and 6.3% in controls; OR, 2.14, 95% CI, 1.01-4.51, P = 0.046) and were associated with susceptibility for disease development. Other polymorphisms were associated with different clinical manifestations. Although HLA-G role in SLE disease is far from being elucidated yet, our association study results along with a systematic review and meta-analysis suggest that HLA-G might be able to slightly modulate the complex SLE phenotype (pooled OR, 1.14, 95% CI, 1.02-1.27, P = 0.021).

Distribution of forensic marker allelic frequencies in Pernambuco, Northestern Brazil. - Santos, S M; Souza, C A; Rabelo, K C N; Souza, P R E; Moura, R R; Oliveira, T C; Crovella, S (Genet Mol Res, 2015)
Pernambuco is one of the 27 federal units of Brazil, ranking seventh in the number of inhabitants. We examined the allele frequencies of 13 short tandem repeat loci (CFS1PO, D3S1358, D5S818, D7S820, D8S1179, D13S317, D16S539, D18S51, D21S11, FGA, TH01, vWA, and TPOX), the minimum recommended by the Federal Bureau of Investigation and commonly used in forensic genetics laboratories in Brazil, in a sample of 609 unrelated individuals from all geographic regions of Pernambuco. The allele frequencies ranged from 5 to 47.2%. No significant differences for any loci analyzed were observed compared with other publications in other various regions of Brazil. Most of the markers observed were in Hardy-Weinberg equilibrium. The occurrence of the allele 47.2 (locus FGA) and alleles 35.1 and 39 (locus D21S11), also described in a single study of the Brazilian population, was observed. The other forensic parameters analyzed (matching probability, power of discrimination, polymorphic information content, paternity exclusion, complement factor I, observed heterozygosity, expected heterozygosity) indicated that the studied markers are very informative for human forensic identification purposes in the Pernambuco population.

Interleukin-18, interleukin-12B and interferon-γ gene polymorphisms in Brazilian patients with rheumatoid arthritis: a pilot study. - Angelo, H D; Gomes Silva, I I F; Oliveira, R D R; Louzada-Júnior, P; Donadi, E A; Crovella, S; Maia, M M D; de Souza, P R E; Sandrin-Garcia, P (Tissue Antigens, 2015)
Polymorphisms in interleukin (IL)-18, IL-12 and interferon (IFN)-γ genes are associated with different levels of cytokines expression and have been associated with rheumatoid arthritis (RA). IL-18 +105 A/C, IL-12B +1188 A/C and IFN-γ +874 T/A polymorphisms were analyzed by restriction fragment length polymorphism-polymerase chain reaction (PCR) and amplification refractory mutation system PCR from 90 RA patients and 186 healthy individuals. There were significant differences to IL-18 +105 A/C polymorphism between the RA and control groups (odds ratio = 3.77; P < 0.0001). Individual carriers of the variant allele C had a 3.77-fold increased risk of for RA (P = 0.0032). No association was observed for IL-12B and IFN-γ polymorphisms. Our finds suggest a possible role for IL-18 polymorphism in the RA susceptibility in studied population.

A rapid screening of ancestry for genetic association studies in an admixed population from Pernambuco, Brazil. - Coelho, A V C; Moura, R R; Cavalcanti, C A J; Guimarães, R L; Sandrin-Garcia, P; Crovella, S; Brandão, L A C (Genet Mol Res, 2015)
Genetic association studies determine how genes influence traits. However, non-detected population substructure may bias the analysis, resulting in spurious results. One method to detect substructure is to genotype ancestry informative markers (AIMs) besides the candidate variants, quantifying how much ancestral populations contribute to the samples' genetic background. The present study aimed to use a minimum quantity of markers, while retaining full potential to estimate ancestries. We tested the feasibility of a subset of the 12 most informative markers from a previously established study to estimate influence from three ancestral populations: European, African and Amerindian. The results showed that in a sample with a diverse ethnicity (N = 822) derived from 1000 Genomes database, the 12 AIMs had the same capacity to estimate ancestries when compared to the original set of 128 AIMs, since estimates from the two panels were closely correlated. Thus, these 12 SNPs were used to estimate ancestry in a new sample (N = 192) from an admixed population in Recife, Northeast Brazil. The ancestry estimates from Recife subjects were in accordance with previous studies, showing that Northeastern Brazilian populations show great influence from European ancestry (59.7%), followed by African (23.0%) and Amerindian (17.3%) ancestries. Ethnicity self-classification according to skin-color was confirmed to be a poor indicator of population substructure in Brazilians, since ancestry estimates overlapped between classifications. Thus, our streamlined panel of 12 markers may substitute panels with more markers, while retaining the capacity to control for population substructure and admixture, thereby reducing sample processing time.

Short Communication FYB polymorphisms in Brazilian patients with type I diabetes mellitus and autoimmune polyglandular syndrome type III. - Addobbati, C J C; de Azevêdo Silva, J; Tavares, N A C; Araujo, J; Guimarães, R L; Brandão, L; Crovella, S; Sandrin-Garcia, P (Genet Mol Res, 2015)
The aim of this study was to perform an association study between seven Fyn-binding protein gene (FYB)-tag single nucleotide polymorphisms (SNPs) and type I diabetes mellitus (T1DM), as well as with disease age of onset. We also assessed the role of FYB SNPs in the insurgence of autoimmune polyglandular syndrome type III (APSIII), characterized by the simultaneous presence of autoimmune thyroid disease and celiac disease, in patients with T1DM from a Northeastern Brazilian population. One hundred and seventy-seven patients with T1DM and 190 healthy individuals were genotyped for seven tag SNPs, covering most of the FYB locus, using real-time polymerase chain reaction amplification. There was no significant difference in the distribution of allele and genotype frequencies among patients and healthy individuals. Moreover, none of the tag SNPs were associated either to T1DM age of onset or to the insurgence of APSIII. However, since the FYB protein is a key component in T cell response, its gene variants might play a role in protein function, which might be testable in a population with different genetic backgrounds or by using functional assays.

Trace samples of human blood in mosquitoes as a forensic investigation tool. - Rabelo, K C N; Albuquerque, C M R; Tavares, V B; Santos, S M; Souza, C A; Oliveira, T C; Oliveira, N C L; Crovella, S (Genet Mol Res, 2015)
Investigations of any type of crime invariably starts at the crime scene by collecting evidence. Thus, the purpose of this research was to collect and analyze an entomological trace from an environment that is similar to those of indoor crime scenes. Hematophagous mosquitoes were collected from two residential units; saliva of volunteers that were residents in the units was also collected for genetic analysis as reference samples. We examined the allele frequencies of 15 short tandem repeat loci (D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, D2S1338, D19S433, vWA, TPOX, D18S51, D5S818, and FGA) and amelogenin. A total of 26 female hematophagous mosquitoes were identified as Aedes aegypti, Aedes albopictus, and Culex quinquefasciatus; we were able to obtain 11 forensically valid genetic profiles, with a minimum of 0.028203 ng/μL of human DNA. Thus, the results of this study showed that it was possible to correlate human genetic information from mosquitoes with the volunteer reference samples, which validates the use of this information as forensic evidence. Furthermore, we observed mixed genetic profiles from one mosquito. Therefore, it is clearly important to collect these insects indoors where crimes were committed, because it may be possible to find intact genetic profiles of suspects in the blood found in the digestive tract of hematophagous mosquitoes for later comparison to identify an offender and/or exclude suspects.

Tumor necrosis factor-α and interleukin-6 gene polymorphism association with susceptibility to celiac disease in Italian patients. - de Albuquerque Maranhão, R M; Martins Esteves, F A; Crovella, S; Segat, L; Eleutério Souza, P R (Genet Mol Res, 2015)
The aim of this research was to study polymorphisms in the genes encoding cytokines interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) in patients with celiac disease (CD) antigens DQ2 (DQ2-positive) or DQ8 (DQ8-positive). We compared the results with healthy controls to determine whether any of the polymorphisms have a role in susceptibility to CD. A case-control of 192 patients with CD (96 DQ2-positive and 96 DQ8-positive) and 96 healthy controls from northeast Italy were included in the study. Analysis of single nucleotide polymorphisms (SNPs) was carried out using the polymerase chain reaction-restriction fragment length polymorphism method. Significant differences for the TNF-α(-308 G>A) polymorphism were observed when we compared the flowing groups: DQ2-positive with controls [odds ratio (OR) = 0.45, P = 0.0002]; DQ8-positive with controls (OR = 3.55, P < 0.0001); and DQ2-positive with DQ8-positive (OR = 0.12, P < 0.0001). We did not observe a statistically significant association between IL-6 (-174 G>C) polymorphism and CD (P > 0.05). Our results suggest that TNF-α(-308 G>A) polymorphism may play a role in susceptibility to CD in Italian patients.

Unusual onset of a case of chronic recurrent multifocal osteomyelitis. - Barrani, M; Massei, F; Scaglione, M; Paolicchi, A; Vitali, S; Ciancia, E M; Crovella, S; Caparello, M C; Consolini, R (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Chronic recurrent multifocal osteomyelitis (CRMO) is a rare condition that commonly affects the clavicle and pelvis. CASE PRESENTATION: We report here a case a 12 years old girl with CRMO arising with recurrent episodes of left supraorbital headache, followed by the appearance of a periorbital dyschromia. Magnetic resonance imaging (MRI) of the skull and orbits revealed an important subacute inflammatory process. Few months after, the child presented a painful swelling of the left clavicle; the histological examination of the related biopsy allowed to establish the diagnosis of CRMO. CONCLUSION: CRMO presenting as acute headache involving neurocranium is rare; to our knowledge this is the first recognized case in the world literature. This pathological condition is frequently misdiagnosed as infection or neoplasm and needs a deep investigation for the differential diagnosis. The physical, laboratoristic and instrumental diagnostic investigations of the patient and the treatment employed are described in detail.

HLA-B35, a common genetic trait, in a familial case of Henoch-Schoenlein purpura and Berger's disease. - Pellegrin, M C; Matarazzo, L; Neri, E; Pennesi, M; Crovella, S (Genet Mol Res, 2014)
Nephritis characterized by IgA mesangial depositions has been described both in Henoch-Schoenlein purpura (HSP) and in Berger's disease (BD), but common genetic traits are still uncertain. We report here the case of two brothers, the first affected by HSP with persistent nephritis and the second by BD, accidentally discovered as silent microhematuria 1 year after HSP onset in the first brother. HLA genotyping demonstrated the presence of HLA-B35 in both patients. Our findings reinforce the need to screen for urinary abnormalities in family members of patients affected by HSP nephritis to identify a silent IgA nephropathy.
Keywords: Adolescent; Child; Female; Genotype; Glomerulonephritis, IGA; HLA-B35 Antigen; Humans; Male; Middle Aged; Nephritis; Phenotype; Purpura, Schoenlein-Henoch

HLA-G 14 bp deletion/insertion polymorphism and mother-to-child transmission of HIV. - Segat, L; Zupin, L; Kim, H-Y; Catamo, E; Thea, D M; Kankasa, C; Aldrovandi, G M; Kuhn, L; Crovella, S (Tissue Antigens, 2014)
The human leukocyte antigen HLA-G, highly expressed at the maternal-fetal interface, has a pivotal role in mediating immune tolerance. In this study we investigated the influence of HLA-G 14 bp insertion polymorphism in human immunodeficiency virus (HIV)-1 mother-to-child HIV-1 transmission. The 14 bp insertion polymorphism was analyzed among 99 HIV-1 positive mothers and 329 infants born to HIV-positive mothers in Zambia, among whom vertical transmission status and timing had been determined. HLA-G 14 bp insertion polymorphism was detected using a custom TaqMan single nucleotide polymorphisms (SNPs) genotyping assay. Logistic regression was conducted to examine the associations between HLA-G alleles and the risk of HIV transmission. The 14 bp insertion allele was more frequent in HIV exposed-uninfected (EU) infants than in infected infants, and was associated with reduced risk of both in utero (IU) and intrapartum (IP) HIV transmission, after adjusting for maternal cluster of differentiation 4 (CD4) cell count and plasma viral load. Maternal HLA-G 14 bp insertion genotype and HLA-G concordance between mother and child were not associated with the risk of perinatal HIV transmission. The presence of the 14 bp insertion associates with protection toward IU and IP HIV infection in children from Zambia, suggesting that HLA-G could be involved in the vertical transmission of HIV.
Keywords: Adult; Alleles; Base Pairing; Child; Genotype; HIV Infections; HLA-G Antigens; Humans; INDEL Mutation; Infant; Infectious Disease Transmission, Vertical; Mothers; Polymorphism, Genetic; Young Adult

HLA-G gene polymorphisms associated with susceptibility to rheumatoid arthritis disease and its severity in Brazilian patients. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Domingues Barbosa, A; Tavares Dantas, A; de Ataíde Mariz, H; F da Rocha, L; Branco Pinto Duarte, A L; Monasta, L; Sandrin-Garcia, P; Crovella, S (Tissue Antigens, 2014)
We analyzed the possible association between human leukocyte antigen-G (HLA-G) genetic variants, supposed to regulate HLA-G expression, and the susceptibility to develop rheumatoid arthritis (RA) as well as its clinical manifestations. The 5'upstream regulatory region (5'URR) and 3'untranslated region (3'UTR) regions of the HLA-G gene were screened in 127 RA patients and 128 controls: 10 5'URR and 3 3'UTR HLA-G polymorphisms as well as two haplotypes were associated with risk for RA development, while a polymorphism in the 5'URR showed an association with the degree of disease activity. These findings, although the number of cases analyzed is limited and the P-values are modest, indicate a possible association between HLA-G gene polymorphisms and susceptibility to develop RA disease and its severity.
Keywords: 3' Untranslated Regions; 5' Flanking Region; Aged; Arthritis, Rheumatoid; Brazil; Disease Progression; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk

Short communication: novel truncating mutations in the CFTR gene causing a severe form of cystic fibrosis in Italian patients. - Lenarduzzi, S; Morgutti, M; Crovella, S; Coiana, A; Rosatelli, M C (Genet Mol Res, 2014)
Cystic fibrosis (CF) is a common recessive genetic disease caused by mutations in the gene encoding for the cystic fibrosis transmembrane conductance regulator (CFTR) protein. More than 1800 different mutations have been described to date. Here, we report 3 novel mutations in CFTR in 3 Italian CF patients. To detect and identify 36 frequent mutations in Caucasians, we used the INNO-LiPA CFTR19 and INNO-LiPA CFTR17+Tn Update kits (Innogenetics; Ghent, Belgium). Our first analysis did not reveal both of the responsible mutations; thus, direct sequencing of the CFTR gene coding region was performed. The 3 patients were compound heterozygous. In one allele, the F508del (c.1521_1523delCTT, p.PHE508del) mutation in exon 11 was observed in each case. For the second allele, in patient No.1, direct sequencing revealed an 11-base pair deletion (GAGGCGATACT) in exon 14 (c.2236_2246del; pGlu746Alafs*29). In patient No. 2, direct sequencing revealed a nonsense mutation at nucleotide 3892 (c.3892G>T) in exon 24. In patient No. 3, direct sequencing revealed a deletion of cytosine in exon 27 (c.4296delC; p.Asn1432Lysfs*16). These 3 novel mutations indicate the production of a truncated protein, which consequently results in a non-functional polypeptide.
Keywords: Alleles; Base Sequence; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; DNA Mutational Analysis; Exons; Female; Heterozygote; Humans; Infant; Infant, Newborn; Italy; Molecular Sequence Data; Mutation; Open Reading Frames; Severity of Illness Index

A comparative analysis of serologic parameters and oxidative stress in osteoarthritis and rheumatoid arthritis: reply to Mishra and colleagues. - Girardelli, M; Bianco, A M; Marcuzzi, A; Crovella, S (Rheumatol Int, 2013)
In chronic diseases such as rheumatoid arthritis and osteoarthritis, the progression of the disease is characterized by stress oxidative, inflammation, and elevated levels of cholesterol. In mevalonate kinase deficiency, an auto-inflammatory disease, the correlation between inflammation and cholesterol levels is opposite. The metabolic pathway that underlies the production of cholesterol is the mevalonate pathway; it is also essential for the biosynthesis of isoprenoids involved in the control of several cell functions. This divergence of cholesterol levels, associated with these two inflammatory disorders, is probably due to a different etiology, pathogenesis, and progression.
Keywords: Arthritis, Rheumatoid; Female; Humans; Inflammation Mediators; Lipids; Male; Osteoarthritis; Oxidative Stress

Association of MBL2 gene exon 1 variants with autoimmune thyroid disease in Brazilian patients. - Filho, C B; Rodrigues, F F; Segat, L; Fonseca, A M; Araujo, J; Arahata, C; Pontes, L; Vilar, L; de Lima Filho, J L; Crovella, S (Int J Immunogenet, 2012)
We investigated the association between MBL2 gene exon 1 functional polymorphisms and autoimmune thyroid disease (AITD) in 163 Brazilian patients (87 with Hashimoto thyroiditis, HT; 76 with Graves' disease) and 214 healthy controls. Individuals carrying MBL2 O allele are at higher risk of developing AITD (OR = 1.58, 95% CI: 1.11-2.26; P-value = 0.009) and HT (OR = 1.67, 95% CI: 1.09-2.55; P-value = 0.013) as suggesting a possible role for mannose-binding lectin in influencing disease susceptibility.
Keywords: Adolescent; Adult; Brazil; Case-Control Studies; Child; Child, Preschool; Exons; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Graves Disease; Hashimoto Disease; Humans; Infant; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

CD14 polymorphisms correlate with an augmented risk for celiac disease in Italian patients. - Catamo, E; Segat, L; Lenarduzzi, S; Petix, V; Morgutti, M; Crovella, S (Genes Immun, 2012)
Celiac disease (CD) is a T-cell-mediated chronic inflammatory disease characterized by autoimmune, immunological and environmental components, where genetic factors in addition to the main known risk factors (gliadin and human leukocyte antigen (HLA)-DQ haplotypes) are supposed to be involved. CD14 is a multifunctional receptor involved in the bacterial lipopolysaccharides-dependent signal transduction. The CD14 gene maps on the long arm of chromosome 5 (5q22-q32), a 'hotbed' region for CD; promoter polymorphisms are known to influence its expression. In this study we analyzed three CD14 promoter polymorphisms (c.-1359G>T, c.-1145A>G and c.-159C>T, ) in 938 CD Italian patients and 533 healthy controls, with known HLA-DQ haplotypes, with the aim of evaluating their possible association with the disease. The c.-1145A>G G and c.-159C>T T alleles (as well as the combination of the two alleles in the GT haplotype), were identified as susceptibility factors for CD development, being significantly more frequent in CD patients than in healthy controls. This association was also confirmed when the analysis was restricted to only those subjects characterized by HLA-DQ risk haplotypes. Our results indicate the involvement of CD14 gene polymorphisms in the susceptibility to CD.
Keywords: Adolescent; Adult; Aged; Antigens, CD14; Case-Control Studies; Celiac Disease; Child; Child, Preschool; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; HLA Antigens; Humans; Infant; Italy; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Frequency of human papillomavirus types 16, 18, 31, and 33 and sites of cervical lesions in gynecological patients from Recife, Brazil. - Baldez da Silva, M F P T; Guimarães, V; Silva, M A R; Medeiros do Amaral, C M; Beçak, W; Stocco, R C; Freitas, A C; Crovella, S (Genet Mol Res, 2012)
Human papilloma virus (HPV) is a well-established cause of cervical cancer. While many studies have been performed so far on HPV viral biology, mode of infection and prevention measures, scanty information is available on lesion sites of infected women and the incidence of viral types at specific locations. We looked for a possible relationship between the most common viral types (HPVs 16, 18, 31, 33) found in Recife, PE, Brazil, and lesion sites. We examined 396 HPV-positive women at the Gynecological Unit of the IMIP at Recife; 288 women were positive for HPV 16, 18, 31, or 33, present as a single-virus type or as co-infection. HPV 16 was the most frequent virus type found in the vulva, vagina, uterine cervix-vagina, and uterine cervix. HPV 31 was the second prevalent virus type in vulva, vagina, uterine cervix-vagina, uterine cervix, and mole. HPVs 18 and 33 were present with similar frequencies in the mole-vulva region. Among the co-infections, HPV 16/18 and HPV16/31 were the most frequent in our study group, followed by HPV 16/33.
Keywords: Adolescent; Adult; Brazil; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; Papillomavirus Infections; Uterine Cervical Diseases; Young Adult

Functional single-nucleotide polymorphisms in the DEFB1 gene are associated with systemic lupus erythematosus in Southern Brazilians. - Sandrin-Garcia, P; Brandão, L A C; Guimarães, R L; Pancoto, J A T; Donadi, E A; Lima-Filho, J L de; Segat, L; Crovella, S (Lupus, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease that results in inflammation and tissue damage. The etiology of SLE remains unknown, but recent studies have shown that the innate immune system may have a role in SLE pathogenesis through the secretion of small cationic peptides named defensins. The aim of the study was to determine the possible involvement in SLE of three functional single nucleotide polymorphisms (SNPs) (c.-52G>A, c.-44C>G and c.-20G>A) in the 5'UTR region of DEFB1 gene, by analyzing them in a population of 139 SLE patients and 288 healthy controls. The c.-52G>A SNP showed significant differences in allele and genotype frequency distribution between SLE patients and controls (p = 0.01 and p = 0.02 respectively) indicating protection against SLE (A allele, OR = 0.68, AA genotype OR = 0.51). Significant differences were also observed for c.-44C>G SNP, the C/G genotype being associated with susceptibility to SLE (OR = 1.60, p = 0.04). Moreover, statistically significant differences between patients and controls were found for two DEFB1 haplotypes (GCA and GGG, p = 0.01 and p = 0.02 respectively). When considering DEFB1 SNPs and SLE clinical and laboratory manifestations, significant association was found with neuropsychiatric disorders, immunological alterations and anti-DNA antibodies. In conclusion, our results evidence a possible role for the c.-52G>A and c.-44C>G DEFB1 polymorphisms in SLE pathogenesis, that can be considered as possible risk factors for development of disease and disease-related clinical manifestations. Additional studies are needed, to corroborate these results as well as functional studies to understand the biological role of these SNPs in the pathogenesis of SLE.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

HLA-G 14bp del/ins genetic variation: association with susceptibility to human immunodeficiency virus-1 vertical transmission but not with human immunodeficiency virus-1 infection through horizontal transmission. - Segat, L; Crovella, S (Tissue Antigens, 2012)
Keywords: Ethnic Groups; Genetic Association Studies; Genetic Predisposition to Disease; HIV Infections; HIV-1; HLA-G Antigens; Humans; INDEL Mutation; Infectious Disease Transmission, Vertical; Polymorphism, Genetic

Letter: inflammatory bowel disease, complementary and alternative medicine, and genetics. - Bianco, A M; Vuch, J; Girardelli, M; Zanin, V; Marcuzzi, A; Crovella, S (Aliment Pharmacol Ther, 2012)
Keywords: Complementary Therapies; Female; Humans; Inflammatory Bowel Diseases; Male; Medication Adherence

Mannose-binding lectin and MBL-associated serine protease-2 gene polymorphisms in a Brazilian population from Rio de Janeiro. - Ferraroni, N R; Segat, L; Guimarães, R L; Brandão, L A C; Crovella, S; Constantino-Silva, R N; Loja, C; da Silva Duarte, A J; Grumach, A S (Int J Immunogenet, 2012)
Mannose-binding lectin (MBL) is a protein able to bind to carbohydrate patterns on pathogen membranes; upon MBL binding, its' associated serine protease MBL-associated serine protease type 2 (MASP2) is autoactivated, promoting the activation of complement via the lectin pathway. For both MBL2 and MASP2 genes, the frequencies of polymorphisms are extremely variable between different ethnicities, and this aspect has to be carefully considered when performing genetic studies. While polymorphisms in the MBL-encoding gene (MBL2) have been associated, depending upon ethnicity, with several diseases in different populations, little is known about the distribution of MASP2 gene polymorphisms in human populations. The aim of our study was thus to determine the frequencies of MBL2 (exon 1 and promoter) and MASP2 (p.D371Y) polymorphisms in a Brazilian population from Rio de Janeiro. A total of 294 blood donor samples were genotyped for 27 polymorphisms in the MBL2 gene by direct sequencing of a region spanning from the promoter polymorphism H/L rs11003125 to the rs1800451 polymorphism (at codon 57 in the first exon of the gene). Genotyping for MASP2 p.D371Y was carried out using fluorogenic probes. To our knowledge, this is the first study reporting the prevalence of the MASP2 p.D371Y polymorphism in a Brazilian population. The C allele frequency 39% is something intermediate between the reported 14% in Europeans and 90% in Sub-Saharan Africans. MBL2 polymorphisms frequencies were quite comparable to those previously reported for admixed Brazilians. Both MBL2 and MASP2 polymorphisms frequencies reported in our study for the admixed Brazilian population are somehow intermediate between those reported in Europeans and Africans, reflecting the ethnic composition of the southern Brazilian population, estimated to derive from an admixture of Caucasian (31%), African (34%) and Native American (33%) populations. In conclusion, our population genetic study describes the frequencies of MBL2 and MASP2 functional SNPs in a population from Rio de Janeiro, with the aim of adding new information concerning the distribution of these SNPs in a previously unanalysed Brazilian population, thus providing a new genetic tool for the evaluation of the association of MBL2 and MASP2 functional SNPs with diseases in Brazil, with particular emphasis on the state of Rio de Janeiro.
Keywords: Adolescent; Adult; Brazil; Ethnic Groups; Exons; Female; Fluorescent Dyes; Gene Frequency; Genetics, Population; Genome, Human; HapMap Project; Humans; Male; Mannose-Binding Lectin; Mannose-Binding Protein-Associated Serine Proteases; Middle Aged; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Analysis, DNA; Young Adult

Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A; Ammadeo, A; Gattorno, M; Not, T; Lepore, L; Crovella, S (Int J Rheumatol, 2011)
Human glycolytic enzyme α-enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti-α-enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.

MBL2 polymorphisms and the choice of controls for association studies: just another story? - Segat, L; Crovella, S (Int J Immunogenet, 2011)
Keywords: Antibodies; Brazil; Control Groups; Gene Frequency; Genetic Association Studies; Genetic Heterogeneity; Genetic Predisposition to Disease; Hepatitis C; Humans; Mannose-Binding Lectin; Polymorphism, Genetic; Thyroid Gland

Analysis of DEFB1 regulatory SNPs in cystic fibrosis patients from North-Eastern Italy. - Segat, L; Morgutti, M; Athanasakis, E; Trevisiol, C; Amaddeo, A; Poli, F; Crovella, S (Int J Immunogenet, 2010)
Cystic fibrosis (CF) transmembrane regulator protein (CFTR) gene is undoubtedly the main genetic factor involved in the modulation of CF phenotype. However, other factors such as human defensins and the genes encoding for these antimicrobial peptides have been hypothesized as possible modifiers influencing airways infection in CF patients, but their role in the pathogenesis of lung disease is still debated. Since DEFB1 gene encoding for human beta-defensin 1 displays features such as antimicrobial or chemotactic activity playing a role in inflammation, it has been considered as a possible candidate CF modifier gene. We analysed three single nucleotide polymorphisms (SNPs) in the 5'-untranslated region of the DEFB1 gene (namely g-52G>A, g-44C>G and g-20G>A) in a group of 62 CF patients from North Eastern Italy, and in 130 healthy controls, with the aim of verifying the possible association of these functional SNPs with the pulmonary phenotype of CF patients. DEFB1 SNPs have been genotyped by using Taqman allele-specific fluorescent probes and a real-time PCR platform. No significant differences were found for allele, genotype and haplotype frequencies of DEFB1 g-52G>A, g-44C>G and g-20G>A SNPs in CF patients stratified for Pseudomonas aeruginosa infection, as well as in patients with a severe and mild clinical phenotype or in patients stratified for CFTR genotypes. DEFB1 allele, genotype and haplotype frequencies of CF patients globally considered were similar to those of healthy controls. Our findings are discordant with respect to another recent study performed on CF patients coming from Southern Italy, probably due to different ethnicity of the patients.
Keywords: 5' Untranslated Regions; Adolescent; Alleles; beta-Defensins; Case-Control Studies; Child; Child, Preschool; Chronic Disease; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Gene Frequency; Genotype; Haplotypes; Humans; Immunity, Innate; Infant; Infant, Newborn; Italy; Male; Polymorphism, Single Nucleotide; Pseudomonas Infections

Mannose-binding lectin is produced by vaginal epithelial cells and its level in the vaginal fluid is influenced by progesterone. - Bulla, R; De Seta, F; Radillo, O; Agostinis, C; Durigutto, P; Pellis, V; De Santo, D; Crovella, S; Tedesco, F (Mol Immunol, 2010)
Mannose-binding lectin (MBL) is a recognition molecule of the complement (C) system and binds to carbohydrate ligands present on a wide range of pathogenic bacteria, viruses, fungi, and parasites. MBL has been detected in the cervico-vaginal cavity where it can provide a first-line defence against infectious agents colonizing the lower tract of the reproductive system. Analysis of the cervico-vaginal lavage (CVL) obtained from 11 normal cycling women at different phases of the menstrual cycle revealed increased levels of MBL in the secretive phase. Part of this MBL derives from the circulation as indicated by the presence of transferrin in CVL tested as a marker of vascular and tissue permeability. The local synthesis of MBL is suggested by the finding that its level is substantially higher than that of transferrin in the secretive phase. The contribution of endometrium is negligible since the MBL level did not change before and after hysterectomy. RT-PCR and in situ RT-PCR analysis showed that the vaginal tissue, and in particular the basal layer of the epithelium, is a source of MBL which binds to the basal membrane and to cells of the outer layers of the epithelium. In conclusion, we have shown that MBL detected in CVL derives both from plasma as result of transudation and from local synthesis and its level is progesterone dependent increasing in the secretive phase of the menstrual cycle.
Keywords: Adolescent; Adult; Body Fluids; Enzyme-Linked Immunosorbent Assay; Epithelial Cells; Female; Humans; Immunohistochemistry; Mannose-Binding Lectin; Menstrual Cycle; Progesterone; Reverse Transcriptase Polymerase Chain Reaction; Vagina; Young Adult